Salt Affected Soils and Their Afforestation - Yadav, J. S. P. (Indian Forester, 1980)
The paper describes the extent and distribution of the salt affected soils in different parts of India. From the management point of view these soils have been grouped into 2 categories (i) Saline soils, (ii) Alkali soils, and their distingushing characteristics have been explained. The work done on the relative tolerance of important forest species for soil salinity and alkali conditions in India as well as in other countries his been briefly summarised, which shows wide differences in the tolerance of the different species. A detailed account has been given or the planting techniques used for raising forest trees on the salt affected soils in India and other counries. It has been shown that the success of the plantations and the improvement in the soil depend to a great extent on the kind of planting techniques and soil working methods followed. Comprehensive details of the various trial. Undertaken on tree plantations in the salt affected soils in different parts of India and other countries have been discussed, which show scope of successful afforestation in certain situations. The systematic data collected through well planned experiments conducted at C.S.I.R.I., Karnal on a calcareous sodic soil canvincingly reveal that species like Prosopis Juliflora, Eucalyptus Hybrid. And Acacia Nilotica can be grown successfully by treating the soil of the planting pit with gypsum and F.Y.M. alongwith application of a small dose of nitrogenous and phosphatic fertilizer. This soil treatment has been found to yield as good results as in the case of replacement of the alkali soil with a normal soil. The various ameliorative effects caused by tree growth on the salt affected soils have been elucidated. The work done recently under pot culture condition. At CSSRI, Karnal with saline water irrigation has shown more adverse effect of salioe water irrigation on Albizzia letbbek than on Eucalyptus hybrid the addition of gypsum, S.Y.M. aad fertilizers appears to minimise the detrimental effects depending upon the composition of saline irrigation water. In view of the limited avaliable data in India a need for intensifying systematic research on critical evaluation of soil Working techniques and identification of suitable tree species for afforestation on the salt affected soils has been suggested.